1118 Outcome of endovascular treatment for symptomatic vertebral artery stenosis: experience in two neurosciences centres. Issue 3 (9th February 2012) - Schulz, U; Kennedy, F; Kueker, W; Clifton, A; Rothwell, P; Markus, H
Abstract : Background: The risk of recurrent stroke in patients with symptomatic vertebral artery (VA) stenosis is high, with a 90-day risk of up to 30%, and a higher risk in intracranial than in VA-origin disease. Angioplasty and stenting are now possible, but more data on procedural and long-term risk are needed to assess the feasibility of trials against medical therapy. We report our experience with endovascular treatment for VA-stenosis over a 10-year period. Methods: We followed up all patients who had stenting or angioplasty for symptomatic VA-stenosis in two neurosciences centres from 2001 to 2011. We determined the occurrence of procedural complications, recurrent stroke, and the presence of restenosis or vessel occlusion on imaging. Results: 50 patients (43 men, mean [SD] age 67 [10] years) were treated from April 2001 to March 2011. 25 patients had distal VA-stenosis. 28 stents, 12 angioplasties, eight angioplasty + stent, two abandoned procedures (poor access) were performed. Periprocedural stroke occurred in three patients (6%), with a higher risk in distal (3/25, 12%) than in proximal (0%, p=0.09) VA-stenosis. During follow-up [median 12 (1–109) months], five patients (10%) had further strokes (three proximal, two distal VA), in only one patient associated with vessel occlusion. Conclusion: In our series, intervention for VA-stenosis was safe, with a procedural risk similar to previous studies. While higher in distal disease, the risk was still lower than the previously reported risk on medical treatment, which is also higher in this group. Data from randomised trials will be vital to inform management of VA-stenosis. VIST (http://www.vist.sgul ac.uk) is such a trial, and is currently recruiting patients.